Gender differences, family size and fertility rate among patients with bipolar disorder: A study from India. (February 2019) - Grover, Sandeep; Sahoo, Swapnajeet; Chaudhary, Swati; Chakrabarti, Subho; Nehra, Ritu; Avasthi, Ajit
Highlights: Significantly higher proportion of male patients had comorbid substance dependence while females had significantly higher prevalence of physical comorbidity. Female reported significantly higher mean number of depressive episodes per year of illness and suicidal attempts. One-fourth (23.3%) of the study sample reported relapse of illness at the time of marriage or immediately following the marriage. Mean number of living children for the couple with one of the partner having bipolar disorder was 1.81 (SD-1.34). About three-fourth (75.3%) of the couples had at least one living child. Abstract: This study aimed to estimate the gender differences, family size and fertility rate among patients with Bipolar disorder (BD). 219 patients diagnosed with BD, who were married for at least 3 years and aged more than 25 years were assessed clinically for the course of illness as per the NIMH-life chart. Fertility and infertility were assessed based on the information on number of living children, abortions and medical termination of pregnancies. Significantly higher proportion of male patients had comorbid substance dependence while females had significantly higher prevalence of physical comorbidity. Additionally, female participants reported significantly higher mean number of depressive episodes per year of illness and suicidal attempts. When marriage was considered as a life event and its association with onset or relapse of illness was evaluated, about one-fourth (23.3%) of the study sample reported relapse of illness at the time of marriage or immediately following the marriage. About one-fourth (24.7%) of the couple with one of the partner having bipolar disorder had no living children even after four years of their marriage. To conclude, this study suggests that there are certain gender differences with regard to the clinical profile and longitudinal course of illness of BD.